PROBLEMS OF INCREASING EXPORTS OF FRUIT AND VEGETABLE PRODUCTS IN THE REPUBLIC OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2026)
The article examines current trends in the development of fruit and vegetable exports in the Republic of Uzbekistan and analyzes the main problems and constraints hindering the growth of the sector’s export potential. Particular attention is paid to issues of logistics, product storage, standardization, certification, and diversification of export markets. Based on the analysis, directions for improving the efficiency of fruit and vegetable exports and strengthening the country’s food security are proposed.